VD_FINDINFO Jug / 2023 / 307 vom 9. November 2022 - VD Tribunal cantonal (2022)
VIOL, CONTRAINTE SEXUELLE, CONSTATATION DES FAITS, VIOLENCE DOMESTIQUE, FIXATION DE LA PEINE | 189 al. 1 CP, 190 al. 1 CP, 47 CP, 49 al. 1 CP, 49 al. 2 CP, 10 CPP (CH)